2013
DOI: 10.1182/blood-2012-05-432104
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of the NLRP3 inflammasome by targeting to promyelocytic leukemia protein in mouse and human

Abstract: Key Points PML selectively activates NLRP3 inflammasome. Targeting to PML could be used to attenuate NLRP3 inflammasome–associated pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 42 publications
(108 reference statements)
2
53
0
Order By: Relevance
“…The reason for this difference is not clear but could be related to the different genetic background of the mice (C57BL/6 versus 129Sv) or the different functions of the multiple isoforms of PML. As Lo et al (34) mentioned, PML appears to inhibit NF-B, a transcription factor required for induction of pro-IL-1␤, so why it would then have a positive role in NLRP3 activation is unclear. More work is clearly needed, but overall both studies confirm an interaction between PML and the NLRP3 inflammasome and highlight the complexity already associated with the many functions of PML.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this difference is not clear but could be related to the different genetic background of the mice (C57BL/6 versus 129Sv) or the different functions of the multiple isoforms of PML. As Lo et al (34) mentioned, PML appears to inhibit NF-B, a transcription factor required for induction of pro-IL-1␤, so why it would then have a positive role in NLRP3 activation is unclear. More work is clearly needed, but overall both studies confirm an interaction between PML and the NLRP3 inflammasome and highlight the complexity already associated with the many functions of PML.…”
Section: Discussionmentioning
confidence: 99%
“…During the preparation of this manuscript, Lo et al (34), published data demonstrating that PML can promote NLRP3 inflammasome activation suggesting that instead of limiting the inflammasome PML might promote its function. The study did not examine an interaction between PML and ASC.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, GBP5 selectively interacts with NLRP3 in response to pathogenic bacteria and soluble ligands, but not with crystalline stimuli (254). Similarly, Lo et al (168) demonstrated that PML-deficient macrophages were impaired for IL-1␤ production and produced less mitochondrial ROS and mitochondrial DNA release. Finally, the RNA-dependent kinase PKR was identified as a general regulator of inflammasome activation, as PKR deficiency impaired the secretion of IL-1␤ in response to a wide variety of stimuli (169).…”
Section: Nlrp3mentioning
confidence: 99%
“…Regulation of the NLRP3 inflammasome by non-NLR proteins [guanylate binding protein 5 (GBP5), promyelocytic leukemia protein (PML), and RNA-dependent protein kinase (PKR)] has more recently been demonstrated by several groups (168,169,254). A study by Shenoy et al (254) revealed GBP5 interacts with the PYRIN domain of NLRP3 and promotes ASC-dependent oligomerization and activation of the inflammasome.…”
Section: Nlrp3mentioning
confidence: 99%
“…Another study, using a genetically distinct murine model, found that PML enhances NLRP3 inflammasome assembly and production of IL-1β, but did not specifically examine interactions between PML and ASC (Lo et al, 2013).…”
Section: Notementioning
confidence: 99%